SAAT UNTUK MENIKAH DALAM UU NOMOR 16 TAHUN 2019: (Tinjauan Hukum Islam Terhadap Batas Usia Menikah) - Luthfia, Chaula; Sopandi, Mariatul Adawiyah; Alicia Hg, Allyah; Pratama, Shaddam; Asmara, Widya Rahmawati (Program Studi Hukum Keluarga Islam, 2025)
The age limit for marriage in Islam is still widely debated and has become an interesting discussion. Unlike the case with the age limit for marriage regulated in Law Number 16 of 2019 concerning Amendments to Law Number 1 of 1974 concerning Marriage. The regulation requires that a man and woman who will perform marriage must be 19 years old. Whereas in Islam the right time to get married is not determined by the exact age. Islam only provides the limits of puberty, common sense, can distinguish between good and bad. Starting from this problem, the compiler was interested in examining the right time to get married which is regulated in article 7 of Law Number 16 of 2019 concerning Amendments to Law Number 1 of 1974 concerning Marriage. This research is a library research, the author uses normative and philosophical approaches. The normative approach is an approach based on legal norms and the concept of shari'ah as well as the rules contained in fiqh and ushul fiqh. Philosophical approach by understanding the problem with the wisdom and purpose contained in a legal determination. The result of this study is that Islam does not explicitly regulate the age limit for marriage, Islam only provides limits through the characteristics or readiness before marriage in some verses of the Qur'an. Setting the age limit for marriage brings benefits by providing opportunities for men and women to have readiness in terms of education, economy, health, psychological, social, biological and religious. These preparations are not explicitly regulated in Islamic law but are in accordance with the intended purpose of marriage, such as creating a family that is sakinah mawaddah and rahmah.